Endoscopic Ultrasonography Findings in Autoimmune Pancreatitis: Be Aware of the Ambiguous Features and Look for the Pivotal Ones - De Lisi, Stefania; Buscarini, Elisabetta; Arcidiacono, Paolo Giorgio; Petrone, Mara; Menozzi, Fernanda; Testoni, Pier Alberto; Zambelli, Alessandro (JOP. Journal of the Pancreas, 2016)
Autoimmune pancreatitis is a form of chronic pancreatitis caused by an autoimmune process. The classical appearance of autoimmune pancreatitis in abdominal imaging is diffuse pancreatic enlargement, but the focal form appears as a mass and often involves the pancreatic head; this scenario represents a challenging diagnostic problem because these features also resemble pancreatic cancer. We present the endoscopic ultrasound findings of seven patients with autoimmune pancreatitis in order to highlight the ambiguous features and the features pivotal for the diagnosis. Image: Hypoechoic focal lesion of the pancreatic head at radial scanning EUS.